Description of Metaprotella haswelliana (Mayer, 1882) (Crustacea: Amphipoda: Caprellidae) from Western Australia with designation of a neotype - Takeuchi, Ichiro; Lowry, James K. (Zootaxa, 2007)
Metaprotella haswelliana (Mayer, 1882), the type species of Metaprotella, was originally described from Port Jackson, New South Wales, Australia and was reported from there in literature published between 1882 and 2003. However, the type specimens are lost and no further specimens could be found in recent surveys in New South Wales waters. The only current records are from Albany, Western Australia and from Port Phillip Bay, Victoria. Based on the materials from Western Australia, the poorly known type species, Metaprotella haswelliana is redescribed, a neotype is assigned, and the genus Metaprotella Mayer, 1890 is redefined.